Pengaturan Kecepatan Motor Shunt Berbasis PID Auto-tune Matlab - Muhlasin; Rukslin (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2018)
The shunt motor cannot produce large currents when starting to do a rotation as in the series coil field. This means that parallel motors have weak initial torque. When the voltage is applied to an electric motor, high resistance to the parallel coil keeps the current flowing slowly. This will affect the motor's rotational speed. To overcome this problem, a PID controller is used which detuning using the Auto tuning program in matlab. From the simulation results it was found that the PID auto tune control method is the best method of three simulated designs. At the speed output the best speed is 300 rpm with the fastest settling time is 0.832 seconds, while the output current is also the best control design with a current of 1,959 amperes and the settling time is 1,523 seconds.